Studi Kualitatif tentang Dinamika dan Tantangan Pengelolaan Aset di Lingkungan Dinas Kesehatan Kabupaten Toraja Utara - Pasapan, Yasri; Adam, Arlin; Alim, Andi (Mando Care Jurnal, 2025)
Regional asset management is a vital component in supporting the efficiency and quality of public services, particularly in the health sector. According to the 2024 Audit Report by the Audit Board of Indonesia (BPK), significant weaknesses remain in the inventory and documentation of regional assets. This study aims to explore the dynamics, challenges, and strategies of asset management within the Health Office of North Toraja Regency. A qualitative approach with a case study design was employed, collecting data through in-depth interviews with key informants, including the head of the office, asset managers, heads of community health centers, and technical staff. Thematic analysis was applied through data reduction, categorization, and conclusion drawing. The results reveal that asset management faces challenges related to technical aspects, coordination mechanisms, and human resources. Key obstacles include the absence of standardized technical SOPs, limited staff capacity, and infrequent data updates. Strategies implemented include the formation of an inventory team and the issuance of a regulatory decree by the Regent. The study recommends strengthening the capacity of asset managers, developing specific SOPs for health assets, and establishing a more integrated and transparent asset information system. These efforts are essential to ensure optimal asset management that supports quality health services in mountainous regions.